2013
DOI: 10.1007/s10879-013-9244-x
|View full text |Cite
|
Sign up to set email alerts
|

Shooting the Messenger: The Case of ADHD

Abstract: Medicating ADHD is a controversial subject that was acutely inflamed in 1995 when high rates of ADHD diagnosis and treatment were documented in southeastern Virginia. Psychologists in southeastern Virginia formed a regional school health coalition to implement and evaluate interventions to address the problem. Other professionals with strong ties to the pharmaceutical industry launched ad hominem attacks on the coalition’s research and work. These attacks contributed to the work being terminated in 2005. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Instead, deviance is medicalized and even if the individual child may not suffer the problem becomes primarily a problem for other people and for the social system. To be observed is that the rate of children being diagnosed with “ADHD” is increasing (Lefever Watson, Arcona, Antonuccio, & Healy, 2014 ; Moncrieff & Timimi, 2011 ; Polanczyk, Willcutt, Salum, Kieling, & Rohde, 2014 ). Pajo and Stuart ( 2012 ) in an analysis of self-help books for parents, whose children are perceived as having “ADHD,” 1 show how these books tend to influence parents to approach their children from a disability perspective.…”
mentioning
confidence: 99%
“…Instead, deviance is medicalized and even if the individual child may not suffer the problem becomes primarily a problem for other people and for the social system. To be observed is that the rate of children being diagnosed with “ADHD” is increasing (Lefever Watson, Arcona, Antonuccio, & Healy, 2014 ; Moncrieff & Timimi, 2011 ; Polanczyk, Willcutt, Salum, Kieling, & Rohde, 2014 ). Pajo and Stuart ( 2012 ) in an analysis of self-help books for parents, whose children are perceived as having “ADHD,” 1 show how these books tend to influence parents to approach their children from a disability perspective.…”
mentioning
confidence: 99%
“…This is comparable to Ireland, where regulatory changes that removed restrictions on the dispensing of amphetamine‐related medications, combined with the marketing of a sustained‐release methylphenidate formulation, contributed to a significant increase in psychostimulant prescribing among General Medical Services children and adolescents between the years 2002 and 2011 . The literature on ADHD suggests that the apparent increase in ADHD observed in this study in 2009 is in part attributable to over‐diagnosis or misdiagnosis of this condition . A study in Australia demonstrated an increase in overall diagnosis of developmental and behavioural problems from 2008 to 2013, with the diagnosis of ADHD rising in new consults from 10% to 14% and review consults from 22% to 28% .…”
Section: Discussionmentioning
confidence: 52%
“…In an aim to advance medication safety for children, an understanding of paediatric prescribing trends is required to identify the type and prevalence of medications prescribed, particularly those that are associated with high‐risk adverse events. To date, most studies on prescribing trends in children have focused on the inpatient setting or on specific drug categories, such as antipsychotics, antidepressants and medications used to treat attention‐deficit/hyperactivity disorder (ADHD) . These studies have revealed important changes in paediatric prescribing over time; however, most reflect a narrow examination of specific drug classes, producing a gap in understanding overall prescribing trends.…”
Section: Introductionmentioning
confidence: 99%
“…First, the steep increase in prescription rates has led to worries of possible overdiagnosis and overtreatment, fuelled initially by a purported lack of clear-cut boundaries between health and disease in psychiatric disorders and, more recently, by the introduction of DSM-5 (Batstra and Frances, 2012;Pierre, 2012). Second, this potential overtreatment has been viewed by some as having been driven more by commercial pressure from pharmaceutical companies than by real medical need (Watson et al, 2014). Third, long-term treatment duration is often not supported by sufficient data on effectiveness and safety (Molina et al, 2009).…”
Section: Limited Public Acceptance Of Treating Children With Medicationsmentioning
confidence: 99%